Analysis of the Development of Maharah Kalam Arabic Mahasantri Center Ma’had Al-Jami’ah Through the Language Division Program - Assabti, Zalaludin (Maliki Interdisciplinary Journal, 2024)
This journal aims to analyze the development of maharah kalam in Arabic among students at the Ma’had Al-Jami’ah Center. The research method used is qualitative with a descriptive analytical approach. Data was collected through observation, interviews and documentation. The research findings showed that there was a significant increase in students’ maharah kalam, which was reflected in their ability to discuss, analyze and construct arguments in Arabic. Factors such as a customized curriculum, interactive teaching methods, and a supportive academic environment contribute to the development of their maharah kalam. The implication of this research is the need to continue to improve teaching methods and a supportive learning environment to facilitate the further development of students’ maharah kalam.